PERLAWANAN KESULTANAN MELAYU JAMBI TERHADAP KOLONIAL BELANDA: KASUS SULTAN MUHAMMAD FACHRUDDIN (1833-1844 M) DAN SULTAN THAHA SAIFUDDIN (1855-1904 M) - Ona Yulita; Doni Nofra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
Disclosure about the formation and development of the Islamic empire in the archipelago, including the underdeveloped field of study. Though the history of the empire in the archipelago is very much to be discussed, both large and small that affect the form of local Islamic traditions and culture. Writing about the sultanate of the archipelago is very little, this is because of limited resources such as local texts, tambo, chronicles, saga, genealogies and so forth. Moreover, an empire in the archipelago that is not too large, will increasingly difficult to express its history and development. Therefore, the study of the Islamic Sultanate in Jambi is a rather neglected study. In fact, according to Azyumardi Azra Jambi is one of the regions in the archipelago that was first visited by Muslim traders from Arabia. The history of the empire in the archipelago is full of tension and conflict, this has made it easier for Western Imperialism to colonize the archipelago. This is not because of its enormous military strength but because of the internal weaknesses of the sultanates in the archipelago who often wage war, intrigue, and try to master each other. One by one the sultanates in the archipelago were controlled, and Western Imperialism took huge profits through the trade routes controlled by the kingdom. The sultanate who was too violent in giving resistance was threatened to be abolished by Western Imperialism.